Chinese culture approached through touch: Chinese cultural heritage learnt via touch-based games - Champion, Erik; Wang, L.; Champion, Erik (IEEE Press, 2012)
Can recent technology help bridge cultures through playful interaction appropriate to traditional tacit means of acquiring knowledge? In order to help answer this question, we designed four Adobe Flash-based based game prototypes and evaluated them via a touch-screen PC. The goal was to offer non-Chinese participants a playful way of experiencing aspects of traditional Chinese culture. The four single-player games were based on the four arts of China (music, calligraphy, painting and the game of Go!). In the evaluation we asked non-Chinese and the Chinese participants to evaluate the games in terms of learning, fun, and cultural authenticity. While this form of tangible computing proved engaging, it raises technical issues of how to convey appropriately the interactive elements without the help of the evaluator, and how to evaluate user satisfaction. We also briefly discuss more embodied and spatial possibilities for projection and interaction.